ANALISIS PROFIL KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV SD NEGERI LOCERET II DALAM PEMBELAJARAN IPS - Siska Nur Wahida (STAI Darul Qalam Tangerang, 2025)
Critical thinking skills are crucial for the development of students' cognitive abilities and influence academic achievement, particularly in social studies, which requires reasoning and appropriate solutions. This study aims to describe the profile of fourth-grade students' critical thinking skills at Loceret II Elementary School in social studies. The study used a qualitative approach using observation, interviews, and documentation techniques. The results indicate that students have varying abilities in each critical thinking indicator. For the